Effects of diabetes mellitus on the rate of carpal tunnel release - علي محمد (Latakia University Journal -Medical Sciences Series, 2023)
This study aims to evaluate the effects of diabetes mellitus DM on the success rate of the carpal tunnel operation by performing surgery on a group of diabetic patients (70 patients. The percentage of females was 65.7% compared to 34.2% of males. The most common age of Entrapment was between 40-49 years. The injury was bilateral in 68.5% of patients and unilateral in 31% of the patients. The study showed that all patients were the owners of stressful work of the wrist. The symptoms were distributed between sensory and motor symptoms together by 58.5% compared to 41.42% who had sensory symptoms only. After performing the carpal tunnel releasing operation for patients, it was found that there was an improvement in symptoms, with a percentage of 92.8%, compared to 7.14%, but there was no improvement or disappearance of symptoms (this is after monitoring for 2 weeks after the surgery.